France : Staff Report for the 2004 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
The staff report for the 2004 Article IV Consultation on France highlights economic performance and near-term outlook and policies. On structural issues, a health care reform has established the key instruments to gain control over the system's budget. Ongoing civil service reform and decentralization are providing the opportunity to realize efficiency gains. Pension and health care reforms have improved the long-term fiscal outlook against the background of the impending demographic shock, while ongoing reforms in product markets are likely to boost growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet